The Effect of Discovery Learning Model on Students’ Critical Thinking Ability in Economics Learning - Ignasius Andre Herdiansyah; Iyan Setiawan; Cucu Suhartini (THE PRESTISE, 2026)
Critical thinking is an essential competence for students in facing real-life challenges, requiring the ability to analyze, evaluate, and synthesize information effectively. However, traditional lecture-based instruction in economics often limits students' opportunities to develop these higher-order thinking skills. This study examines the effect of the Discovery Learning model on students' critical thinking abilities in economics learning at the high school level. A quasi-experimental method with a non-equivalent control group design was employed, involving class X students at SMA Negeri 1 Ciniru. The experimental group received instruction through the Discovery Learning model, which emphasizes student-centered exploration and knowledge construction, while the control group used conventional lecture methods. Data were collected using pre-test and post-test instruments measuring critical thinking competencies, and analyzed using N-Gain and t-test procedures. The findings demonstrate that Discovery Learning significantly enhances students' critical thinking abilities compared to traditional instruction, with the experimental group showing substantial improvement in higher cognitive categories. These results align with constructivist theories proposed by Bruner, Ennis, and Paul & Elder, confirming that active learning approaches facilitate deeper cognitive development. However, implementation challenges including time constraints and classroom management complexities were identified. Future research should explore larger, more diverse samples and investigate the integration of complementary pedagogical strategies to optimize learning outcomes.